Irrigation scheduling for corn in a coastal saline soil - Tingting, Chang; Xiaohou, Shao; Huan, Ye; Wei, Li; Jie, Zhang; Zhanyu, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Currently, water scarcity is serious and the irrigation scheduling with efficient water use becomes important in China. In this study, irrigation systems were scheduled in the saline area along Laizhou Bay. Field study was conducted to determine the relation of irrigation regime and crop yield from 2010 to 2012, and the representative rainfall years (high-flow year, normal-flow year and low-flow year) were calculated by analyzing rainfall frequency over 30 years. Six irrigation regimes were set according to local farmers’ practices. Irrigation amounts of T1, T2, T3, T4, T5 and T6 were 225.0 mm, 270.0 mm, 337.5 mm, 300.0 mm, 360.0 mm and 450.0 mm, respectively, with the same frequency of four times. The results showed that soil salt content decreased with the increase of irrigation water amounts. The corn yield varied from 6560 kg/hm2 to 8060 kg/hm2. The highest yield was obtained from T5. Production functions related to irrigated water (I, mm) for corn yield (Y, kg/hm2) was Y = −0.0397I2 + 1059.6 (R2 = 0.8892). Aiming at high corn yield, total water supply (irrigation and rainfall) to corn crops was 859 mm. Precipitation amounts at low-flow year (p=80%), normal-flow year (p=50%) and high-flow year (p=20%) were obtained by the simulation of rainfall frequency curve, which were 348 mm, 457 mm and 604 mm respectively in the whole growth period (from late June to mid-October). In order to obtain the highest theoretical corn yield, according to field results and rainfall, the optimum irrigation frequency at low-flow year, normal-flow year or high-flow year was four times for corn in the saline area along Laizhou Bay. Keywords: corn (Zea mays), irrigation regime, desalination, rainfall, soil salinity DOI: 10.3965/j.ijabe.20160906.2133 Citation: Chang T T, Shao X H, Ye H, Li W, Zhang J, Zhang Z Y. Irrigation scheduling for corn in a coastal saline soil. Int J Agric & Biol Eng, 2016; 9(6): 91-99.